Increased concentrations of tumour necrosis factor in "cachectic" patients with severe chronic heart failure. - McMurray, J (1991)
OBJECTIVE--To ascertain whether patients with cardiac failure and reduced body weight ("cardiac cachexia") have increased circulating concentrations of tumour necrosis factor (cachectin). DESIGN--Patients with cardiac failure were prospectively identified as "cachectic" (body fat less than 27% in men and less than 29% in women measured by skinfold thickness callipers) or "non-cachectic". Tumour necrosis factor was assayed blind to patient group. SETTING--Cardiology unit in a tertiary referral centre. PATIENTS--26 consecutive patients (10 women) (mean age 61) admitted for investigation or treatment of chronic heart failure. All were in New York Heart Association class III or IV. RESULTS--In nine of the 16 cachectic patients the concentration of tumour necrosis factor was increased (mean (SEM) 74 (20) pg/ml) compared with one of the 10 "non-cachectic" patients (22 pg/ml, p less than 0.001). Patients with a raised circulating concentration of tumour necrosis factor weighed significantly less (55.6 (3.5) kg) than those in whom the concentration of tumour necrosis factor was normal (69.0 (4.1) kg) (p = 0.02). CONCLUSIONS--Circulating concentrations of tumour necrosis factor were increased in a significant proportion of patients with chronic heart failure and low body weight. Tumour necrosis factor stimulates catabolism experimentally and it may be a factor in the weight loss seen in patients with "cardiac cachexia".